Selective Enrichment of Genomic Loci for the Noninvasive Detection of Fetal Aneuploidies [285]. (May 2015) - Jensen, Taylor J.; Deciu, Cosmin; Ehrich, Mathias; Geis, Jennifer; Kim, Sung K.; Tao, Helen
Abstract : INTRODUCTION: Current commercial offerings for noninvasive prenatal testing differ in the breadth of their coverage (whole genome or reduced content). Although whole genome methods provide an unbiased view of the entire genome and thus the potential detection of a broad array of genomic aberrations, reduced content methods provide efficiency for detecting a limited set of copy number variations. The objective of this study was to develop and evaluate a noninvasive prenatal testing assay focused on the selective enrichment and analysis of a subset of the genome. METHODS: Regions for evaluation were selected using a combination of bioinformatic and experimental methods. Circulating cell-free DNA was extracted from the plasma of pregnant donors and amplified using multiplexed amplification in a single well targeting more than 50 genomic loci. Amplified products were then evaluated using multiple methods including matrix-assisted laser desorption/ionization–time-of-flight mass spectrometry and massively parallel sequencing. RESULTS: We evaluated the performance of the developed assay in an unblinded set of 288 circulating cell-free DNA samples from pregnant donors with known fetal karyotypes including 258 euploid and 30 aneuploid samples. These samples were measured using multiple technologies including matrix-assisted laser desorption/ionization–time-of-flight mass spectrometry and massively parallel sequencing. Using these methods, 28 of the 30 aneuploid samples were detected with a specificity ranging from 0.95 to 0.99, depending on the chromosome. CONCLUSION AND IMPLICATION: Taken together, these proof-of-concept data demonstrate the feasibility of leveraging selected genomic loci for a low-cost, platform-flexible method for the noninvasive detection of fetal autosomal aneuploidies.